Believability of negative automatic thoughts : psychometric properties of the Automatic Thoughts Questionnaire – Modified Version - Sævar Már Gústavsson 1991- (2016)
The cognitive theory of depressions proposes that depression is maintained by maladaptive thinking patterns that affect how persons understand their experiences. Cognitive behavioural therapy is supposed to alleviate the symptoms of depression by cognitive change, and the evidence suggests that cognitive change leads to symptom reduction. However, it is poorly understood what psychological interventions are necessary and sufficient for this cognitive change. One hypothesis of how cognitive change occurs is through reducing believability of negative, unrealistic thoughts and increasing believability of alternative more realistic thoughts. To test this hypothesis of mechanism of change in treatment of depression a measurement is needed that measures believability of negative thoughts. This study reports information about preliminary validation of a modified version of the Automatic Thoughts Questionnaire (ATQ-MV) in a sample of university students in Iceland. The ATQ-MV assesses frequency of negative automatic thoughts, as well as measuring how much the respondent believed those thoughts the last time he was depressed/sad on a scale from 0% to 100%. The results indicate that the ATQ-MV is a reliable measurement, but further research is needed to further establish its reliability. The ATQ-MV has adequate convergent validity, but discriminant validity needs to be assessed further. Exploratory factor analysis indicated that one factor solution was the most appropriate in the sample used in the study. Questions are raised about the reliability of the response format of the ATQ-MV because respondents did not seem to fully understand the instructions. Alterations to the ATQ-MV are proposed and further research’s discussed. Keywords: depression, cognitive behavioural therapy, negative automatic thoughts